Fulbright paradox and the end of the unipolar world (polemical notes) - Antonovich, Ivan I. (Journal of the Belarusian State University. Sociology, 2022)
The article is an attempt to analyse the consequences of the American and NATO defeat in Afghanistan, which is a demonstration of the inability of the Anglo-Saxon strategy of world dominaton to build a unipolar world, where the United States and their allies would control the world situation. The situation is developing in a way, which has no place for the Anglo-Saxon strategy of world domination.